Evaluation of Mobile Applications User Interfaces: A Case Study of Children’s Mobile Applications - Algashmari, Wajd Fahad; Aljedebi, Wajdi (Communications in Mathematics and Applications, 2022)
Phones developed from devices that provide simple service into more complex services providers where many application and opportunity are available to users such as taking pictures, playing games, editing videos and pictures, documents viewing etc. All of these enhancements lead to strong attachment between smartphones and people. Applications developed to meet users’ needs in different range of the society to hit high production and increase sales. Developer of these application taken under their consideration different characteristics that effect the performance and users adoption, where User Interfaces UI is one of the most critical part as it is the first interaction gate between users and the application. Evaluation of this part is necessary in order to get highly preferable application by the user, where evaluation is performed with users and without them. These two approaches used in this paper to evaluate children applications. Shneiderman’s golden rules used in usability measurement in addition to some criteria of the Software Usability Measurement Inventory SUMI by observing group of children while interacting with chosen application.